Rice germin-like proteins: allelic diversity and relationships to early stress responses - Davidson, Rebecca M.; Manosalva, Patricia M.; Snelling, Jacob; Bruce, Myron; Leung, Hei; Leach, Jan E. (Springer, 2010)
Germin-like protein (GLP) markers were associated with quantitative trait loci (QTL) for resistance to the rice blast pathogen, Magnaporthe oryzae in multiple rice (Oryza sativa) mapping populations. Twelve paralogous OsGLP gene family members are located within the physical QTL region on chromosome 8, and gene silencing studies suggest that they contribute collectively to the resistance phenotype. We compared sequence and expression profiles of OsGLP alleles in two resistant and two susceptible parental rice lines to find functional polymorphisms that correlated with the resistant phenotype. Based on coding and promoter sequences, the genes belong to two germin subfamily groups (GER3 and GER4). OsGLP members from both subfamilies were constitutively expressed and developmentally regulated in all cultivars. Transient induction above constitutive levels was observed for some OsGLPs, especially GER4 subfamily members, at early time points after M. oryzae infection and mechanical wounding. Varying 5′ regulatory regions and differential expression of some family members between resistant and susceptible cultivars corresponded with differential hydrogen peroxide (H2O2) accumulation after the same stimuli. OsGLP of both GER subfamilies localized to the plant cell wall. The protein location and early gene induction suggest that OsGLPs protect rice leaves at early stages of infection before fungal penetration and subsequent ingress. Our data suggest that regulation of OsGLP genes defines resistant versus susceptible phenotypes.